Programming Netscape plug-ins - Oliphant, Zan (Sams Net, 1996)
A resource which explains how to write dynamically loaded code modules for Netscape's Navigator. Arrangement is in four sections which cover getting started, Netscape Plug-Ins basics, examples, programming resources for Windows, and appendixes which provide a listing of available plug-ins, and a glossary of terms. Other topics include understanding MIME, memory management, MCIWnd, MIDI, Netscape's LiveConnect, and debugging with Socket Spy.